Preclinical evaluation of ELP‐004 in mice - Jamie L. McCall; Werner J. Geldenhuys; Lisa J. Robinson; Michelle R. Witt; Peter M. Gannett; Björn C. G. Söderberg; Harry C. Blair; Jonathan Soboloff; John B. Barnett (Wiley, 2024)
Abstract This study provides a detailed understanding of the preclinical pharmacokinetics and metabolism of ELP‐004, an osteoclast inhibitor in development for the treatment of bone erosion. Current treatments for arthritis, including biological disease‐modifying antirheumatic drugs, are not well‐tolerated in a substantial subset of arthritis patients and are expensive; therefore, new treatments are needed. Pharmacokinetic parameters of ELP‐004 were tested with intravenous, oral, and subcutaneous administration and found to be rapidly absorbed and distributed. We found that ELP‐004 was non‐mutagenic, did not induce chromosome aberrations, non‐cardiotoxic, and had minimal off‐target effects. Using in vitro hepatic systems, we found that ELP‐004 is primarily metabolized by CYP1A2 and CYP2B6 and predicted metabolic pathways were identified. Finally, we show that ELP‐004 inhibits osteoclast differentiation without suppressing overall T‐cell function. These preclinical data will inform future development of an oral compound as well as in vivo efficacy studies in mice.